Implementasi Student Centered Learning (SCL) Materi Olimpiade Sains Nasional (OSN) Kebumian Di SMA Negeri 8 Gowa, Sulawesi Selatan - Ulva Ria Irvan; Ilham Alimuddin; Meutia Farida; Adi Maulana; Asri Jaya; Haerany Sirajuddin; Adi Tonggiroh; Busthan Azikin; Sahabuddin - (Faculty of Engineering UNHAS, 2019)
The development of scientific subjects in geography at the secondary school level has an impact on knowledge about geology, including rocks and their formation processes, the origin of the earth, to how to plan urban planning in a geographic information system. Geography books generally refer to the international earth science curriculum, making it very difficult for high school students to understand it. The main problem revealed by teachers and students who are interested in OSN in the field of earth is that the material being contested is quite complex. The basic problems of geology, spatial planning and disaster become national and even global issues. Through the Community Service Program activities, the Faculty of Engineering in this case is represented by a team of lecturers from the Geological Engineering Study Program offering Student Centered Learning methods to facilitate understanding of the National Science Olympiad material in the field of Earth Sciences. Besides that, it can also motivate and competitiveness to take part in competitions, especially for students of SMA Negeri 8 Gowa. The purpose of community service activities is to: a) Provide basic geological knowledge as part of earth science; b) Providing knowledge of Indonesian geology; c) Provide material tested in the national earth science olympiad; d) Provide the practice of identifying minerals and rocks, geological structures, fossils, and topographic map readings.